Searching for Reorganization Realities - Elizabeth Warren; Jay Lawrence Westbrook (Washington University Law Quarterly, 1994)
The study, which is described in more detail below, is a projected five-year longitudinal analysis of business bankruptcy cases filed in twenty-three federal districts during calendar year 1994. Because the information presently available from systematic empirical studies on business bankruptcy is so limited, our study necessarily must be devoted in large part to establishing baseline data about this sort of legal proceeding. But we have room within this framework to explore other visions of what data are important.
Keywords: Bankruptcy reorganization; United States; Corporate reorganizations